5(x+3)-7x=27

Simple and best practice solution for 5(x+3)-7x=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)-7x=27 equation:


Simplifying
5(x + 3) + -7x = 27

Reorder the terms:
5(3 + x) + -7x = 27
(3 * 5 + x * 5) + -7x = 27
(15 + 5x) + -7x = 27

Combine like terms: 5x + -7x = -2x
15 + -2x = 27

Solving
15 + -2x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -2x = 27 + -15

Combine like terms: 15 + -15 = 0
0 + -2x = 27 + -15
-2x = 27 + -15

Combine like terms: 27 + -15 = 12
-2x = 12

Divide each side by '-2'.
x = -6

Simplifying
x = -6

See similar equations:

| 2nsquared-3n-20=o | | -13=1-5x+7x | | -3a+7y+7a-5y= | | 4u-3=9 | | 15+6m=3(8m+5) | | x+58=105 | | 4y-4+y+24=6y+20-3y | | 5n+7n=4+92 | | 5+19r-2=9r+15-2r | | 4y^3-7y^2+28=16 | | -7b+5(b-3)=3(5+7b) | | 2(2x+9)=3x+6 | | -4+7+(-4)= | | -36/45= | | -7-7(-7)= | | 32y+12y+3x-5= | | x^3+5x-210=0 | | -5y+23=-8(y-4) | | 2(2x+4)=3x+9 | | lg(1+x)=1+lgx | | 8y-3y+4n= | | Log(9)+log(15)= | | 3/40-1/30 | | 28=5n | | 3x^2+23x+13=0 | | 0.02(6x-3)=0.12(x-2)+0.18 | | 82+40x=62-30x | | N-10/7=10 | | 6x+18y=-9 | | .82+.4x=.62-.3x | | 13w-8w=40 | | 6b+7b-10+2= |

Equations solver categories